2016
DOI: 10.1074/jbc.m116.745653
|View full text |Cite|
|
Sign up to set email alerts
|

Mesenchymal Stromal Cell-derived Extracellular Vesicles Promote Myeloid-biased Multipotent Hematopoietic Progenitor Expansion via Toll-Like Receptor Engagement

Abstract: Edited by Dennis VoelkerMesenchymal stromal cells (MSCs) present in the bone marrow microenvironment secrete cytokines and angiogenic factors that support the maintenance and regenerative expansion of hematopoietic stem and progenitor cells (HSPCs). Here, we tested the hypothesis that extracellular vesicles (EVs) released by MSCs contribute to the paracrine crosstalk that shapes hematopoietic function. We systematically characterized EV release by murine stromal cells and demonstrate that MSC-derived EVs promp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 56 publications
1
52
0
Order By: Relevance
“…e colocalization of TLR4 and Rab5 can be observed in bone marrow-derived macrophages and hematopoietic stem cells, and progenitor cells upon lipopolysaccharide stimulation [96]. Rab5 affects both TLR4 downstream NF-κB signaling and the downstream of target genes, such as Hif-1 and CCL2, ultimately promoting the amplification of bone marrowderived multifunctional hematopoietic stem cells [97].…”
Section: Rab5 and Antigen Recognitionmentioning
confidence: 99%
“…e colocalization of TLR4 and Rab5 can be observed in bone marrow-derived macrophages and hematopoietic stem cells, and progenitor cells upon lipopolysaccharide stimulation [96]. Rab5 affects both TLR4 downstream NF-κB signaling and the downstream of target genes, such as Hif-1 and CCL2, ultimately promoting the amplification of bone marrowderived multifunctional hematopoietic stem cells [97].…”
Section: Rab5 and Antigen Recognitionmentioning
confidence: 99%
“…Another report showed that various types of body fluid EVs (exosomes) induced NFκB‐ and STAT3‐mediated secretion of inflammatory cytokines in TLR‐dependent fashion (Bretz et al, ). Furthermore, murine MSC‐derived EVs promoted myeloid‐biased multipotent haematopoietic progenitor expansion via TLR4 engagement (Goloviznina et al, ). Collectively, these observations indicate that TLR4/NFκB signalling pathway is a potential target of EVs.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that EVs may impair the assembly of TLR4 multireceptor complex and affect signal transduction from the plasma membrane. Although there is no experimental evidence about direct interaction between EVs and components of TLR4 multireceptor complex (TLR4 receptor, LPS binding protein, MD2, and CD14), recent report demonstrated quantitative colocalization of myristoylated tomato‐tagged EVs and TLR4 receptors (Goloviznina et al, ). EVs can also act as carriers for the endogenous TLR4 ligands.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, HSPC LSK cells showed prominent expansion of myeloid progenitor cells with MyD88‐dependent signaling when subjected to MSC‐EVs with the upregulation of nuclear factor‐κB (NF‐κB). This effect was abolished in the presence of a TLR4 inhibitor indicating TLR4 receptor involvement (Goloviznina et al, 2016).…”
Section: Role Of Evs In Hematopoiesis/hematological Malignanciesmentioning
confidence: 99%